2019
DOI: 10.1210/clinem/dgz185
|View full text |Cite
|
Sign up to set email alerts
|

Dissecting the Role of Thyrotropin in the DNA Damage Response in Human Thyrocytes after 131I, γ Radiation and H2O2

Abstract: Background The early molecular events in human thyrocytes after 131I exposure have not yet been unravelled. Therefore, we investigated the role of TSH in the 131I-induced DNA damage response and gene expression in primary cultured human thyrocytes. Methods Following exposure of thyrocytes, in the presence or absence of TSH, to 131I (β radiation), γ radiation (3 Gy), and hydrogen peroxide (H2O2), we assessed DNA damage, prolif… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 58 publications
0
4
0
Order By: Relevance
“…However, none of these were found in the present study. In vitro studies on thyroid cells have shown that DNA damage after 131 I exposure increases in the presence of high levels of TSH [57]. Thyroid function has also been evaluated, by measurements of the IL-6 TNF-αand NO proteins in serum samples using a rat model using four week old rats irradiated with 5.5 MBq 131 I [58].…”
Section: Upstreammentioning
confidence: 99%
“…However, none of these were found in the present study. In vitro studies on thyroid cells have shown that DNA damage after 131 I exposure increases in the presence of high levels of TSH [57]. Thyroid function has also been evaluated, by measurements of the IL-6 TNF-αand NO proteins in serum samples using a rat model using four week old rats irradiated with 5.5 MBq 131 I [58].…”
Section: Upstreammentioning
confidence: 99%
“…In in vivo transgenic mice models, TSH signaling was required for BRAFV600E-induced thyroid tumorigenesis, but also conferred more aggressive features in BRAFV600E-induced thyroid tumours [15,30]. In vitro, it was shown that TSH induced DNA damage in human thyrocytes, probably through an increase in intracellular levels of reactive oxygen species (ROS) [31].…”
Section: Discussionmentioning
confidence: 99%
“…For example, polyamines effectively prevent bone loss in ovariectomized mice [ 20 ]. In addition, polyamine reduction leads to increased H 2 O 2 and ROS levels, which, as previously mentioned, contribute to inflammatory diseases [ 63 ]. Therefore, we propose that preventing polyamine decline, for example by repressing or inhibiting PAOX, could be a potential treatment for alleviating postmenopausal symptoms.…”
Section: Discussionmentioning
confidence: 99%